Before Equiano : A Prehistory of the North American Slave Narrative - Hutchins, Zachary McLeod (Book collections on Project MUSE., 2022)
"In the antebellum United States, formerly enslaved men and women who told their stories and advocated for abolition helped establish a new genre with widely recognized tropes: the slave narrative. This book investigates how enslaved black Africans conceived of themselves and their stories before the War of American Independence and the genre's development in the nineteenth century. Zachary McLeod Hutchins argues that colonial newspapers were pivotal in shaping popular understandings of both slavery and the black African experience well before the slave narrative's proliferation. Introducing the voices and art of black Africans long excluded from the annals of literary history, Hutchins shows how the earliest life writing by and about enslaved black Africans established them as political agents in an Atlantic world defined by diplomacy, war, and foreign relations. In recovering their stories, Hutchins sheds new light on how black Africans became Black Americans; how the earliest accounts of enslaved life were composed editorially from textual fragments rather than authored by a single hand; and how the public discourse of slavery shifted from the language of just wars and foreign policy to a heritable, race-based system of domestic oppression."--